Leveraging Systems Thinking to Manage Learning Organisations: An Analysis of the Service Sector. - Gupta, Manisha; Singh, Mamta; Kumari, Ranjani (Systems Research & Behavioral Science)
This study investigates the role of systems thinking in fostering learning organisations within the service industry. Specifically, it explores how interactivity, process orientation and awareness of mental models contribute to the development of learning organisations. Data were collected using a judgmental sampling method from 246 respondents in the service sector. Partial least squares structural equation modelling was employed to analyse the relationships. To complement the empirical analysis, a causal loop diagram was developed to visualise the dynamic feedback loops among systems thinking dimensions. The findings reveal that interactivity, process orientation and mental model knowledge significantly enhance the development of learning organisations by promoting teamwork, structured problem‐solving and knowledge integration. However, dynamic thinking showed no significant effect, suggesting a context‐specific boundary condition where immediate operational responsiveness may overshadow long‐term learning priorities. This research offers both empirical and systems‐based insights, providing practical guidance for managers to apply systems thinking strategically and holistically.